Fano Resonance of the Symmetry-Reduced Metal Bar Grating Structure. (16th October 2014) - Xie, Suxia; Li, Zhijian; Zhou, Renlong; Zhan, Jie; Liu, Qiong; Wu, Lingxi; Zhou, Bingju
Abstract : We demonstrate that Fano resonance and even multipole Fano resonance can be obtained in a symmetry-reduced structure composed of gold bars with different bar sizes or bar shapes on a layer of dielectric. There is a transparency window opened within the frequency region of the absorptive dipole resonance by metallic bars, as long as the narrow grating waveguide mode induced by reducing symmetry is coincided in spectrum with the dipole resonance such that a destructive interference happens between these two resonant modes. Line shape of the transmission spectra of the nanostructure can be modulated effectively by changing the size or shape of the series of metal bars. The results found can be useful in the design of novel optical device.